Pertanggungjawaban Pidana Pelaku Pembunuhan dalam Keadaan Mabuk Akibat Konsumsi Minuman Keras: Studi Kasus Putusan Nomor 151/Pid.B/2023/Pn Dpk - angelo lumban raja; Adensi timomor; Wenly Ronald Jefferson Lolong (Jurnal Hukum Lex Generalis, 2026)
This study examines criminal liability and the proof of intent in homicide committed under the influence of alcohol. It aims to analyze the regulation of criminal liability under Law No. 1 of 2023 and the judicial considerations in Decision Number 151/Pid.B/2023/PN Dpk. The study employs a normative juridical method with a case approach. The findings indicate that voluntary intoxication cannot serve as a ground for excluding criminal liability. The court considered such a condition as a self-created danger, thereby fulfilling the element of intent (dolus eventualis) and held the offender criminally liable based on the principle of geen straf zonder schuld. It is recommended that law enforcement strengthen the proof of intent in similar cases. This finding confirms that voluntary intoxication does not absolve the perpetrator of criminal liability for their actions.